Effect of TiB2 particles on high temperature wear and friction behaviour of AA7075 composites fabricated through squeeze cast technique. (2021) - Loganathan, P.; Gnanavelbabu, A.; Rajkumar, K.
Abstract: AA7075/Titanium diboride (TiB2 ) composites with different weight percent (5, 10, and 15 wt%) composites were successfully fabricated through squeeze casting technique. Optical Microscope (OM), phase analysis using X-ray Diffraction (XRD), to determine the distribution of particles and phase identification. The sliding wear behaviour of AA7075/TiB2 (5, 10, 15 wt%) were conducted in elevated temperature (70, 105, 140, 175, 210, 245 °C). The hardness of composites increased to a maximum of 7.76%, 17.82%, and 24.80% respectively while adding TiB2 particles. XRD pattern indicates the presence of Al and TiB2 particles without the presence of any other deleterious intermetallic compounds. The optical micrograph revealed a homogeneous distribution of TiB2 particles and bonded with a matrix material. The wear resistance of AA7075/15 wt% TiB2 shows a 30.78% improvement in wear resistance as compared to the AA7075 matrix material. The formation of a stable tribo layer improved higher wear resistance in all working temperatures. The worn surface analysis of tested samples was carried out using a Scanning Electron Microscope (SEM) it revealed adhesion, oxidation and delamination are the main modes of wear mechanisms of alloy and composite with increasing temperature.